Getting started in journalism - Harkrider, Jack. 4 0 16; 5 (New York : McGraw Hill/Glencoe, 1997)
Contains over seventy detailed activities that help to develop journalism skills for beginners including tips on writing and editing news and feature stories, generating ideas, and producing a newspaper.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Vocational guidance. -- Journalism;Vocational guidance; 20; 2